Study of the thermal behavior in solid state of Mn(II)-Diclofenac complex - Kobelnik, Marcelo; Quarcioni, Valdecir Ângelo; De Almeida, Adélia Emília [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (My University, 2018)
The preparation, characterization and thermal behavior of Mn(II)-diclofenac solid-state complex was investigated by simultaneous TG/DTA and DTG curves, DSC, X-ray powder diffraction (XRD) and scanning electron microscopy (SEM) techniques. The thermal evaluation was carried out with sample masses of 2 and 5 mg, with the purpose of comparing the values of activation energy regarding dehydration, monotropic phase transition and thermal decomposition in both samples mass. The DSC curves were obtained in opened and with crimped lids crucibles of aluminum under oxygen purge gas and static air (without purge gas). The DTA and DSC curves show an exothermic peak between 150-180 °C depending on heating rate, which can be attributed to the monotropic non-reversible reaction. The activation energy (Ea/kJ mol-1) to dehydration, the monotropic phase transition and the first thermal decomposition step were determined by Capela-Ribeiro nonlinear isoconversional method. The activation energy under oxygen dynamic purge gas shows lower values compared to those obtained under static air.
Keywords: Activation energy; Mn(II)-diclofenac complex; Monotropic reaction; Thermal analysis